Keinginan Penerapan Program Keluarga Berencana (KB) pada Remaja untuk Masa Mendatang di Provinsi Bengkulu - Iis Suryani; Sarah Handayani (Universitas Muhammadiyah Semarang, 2021)
Background: The government seeks to improve the quality of life of adolescents through coaching related to the generation planning program in order to provide understanding and strengthen family planning in the future, including participation in the Family Planning (KB) program. Objective: This study aims to determine the factors related to the desire of adolescents in implementing family planning programs in the future in Bengkulu Province. Methods: Cross sectional research design with secondary data from the Family Performance and Accountability Survey (SKAP) in 2019. The research sample was 341 unmarried adolescents aged 10-24 years in Bengkulu Province with data analysis using the chi square test. Results: The results of statistical tests showed three variables were significantly associated with desire of adolescent in implementing the family planning in the future namely knowledge (p=0.005), place of residence (p=0.000) and sources of information (p=0.009). Meanwhile, the variables of age (p-value 1.686) and level of education (p-value 0.277) are not significantly associated. Conclusion: place of residence, access to information and knowledge of adolescents about various contraceptive methods are factors related to the desire of adolescents in implementing family planning programs in the future. It is recommended that there be periodic assistance from the National Population and Family Planning Agency (BKKBN) to optimize the role of the Youth Counseling Information Center (PIK-R) in schools in order to provide motivation to adolescents in planning their future families.